Evaluation of Cranberry as a Novel Therapeutic Strategy for Intracerebroventricular (ICV) Quinolinic Acid-induced Cognitive Impairment in Rats - Tao, Li; Kumari, Deepika; Badam, Sai Kumar; Kaur, Harpreet; Dalwal, Vikrant; Kumari, Pallvi; Kainth, Ritu (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: neuroprotection